Material for joint member containing woody biomass roasted material
Patent Information
- Application Number
- JP2023148221
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0009】 本発明の接合部材用材料は、石油資源由来の合成樹脂の含有量を抑制していながら、超音波溶着強度が優れる。
Smart Images

Figure 2025041125000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a material for a joining member, comprising wood-based biomass roasted material and a thermoplastic resin. [Background technology]
[0002] In recent years, biomass materials have been widely used in the materials field as an alternative to fossil fuels, from the perspective of measures against global warming and building a recycling-oriented society. Biomass materials are materials derived from living organisms such as plants. As biomass materials are organic, they emit carbon dioxide when burned. However, the carbon contained in them comes from the carbon dioxide absorbed from the atmosphere by the biomass through photosynthesis during its growth, so it is said that the use of biomass materials does not increase the amount of carbon dioxide in the atmosphere overall. This property is called carbon neutral.
[0003] As a way of putting the carbon neutral concept into practice, many technological developments have been made regarding wood flour-filled resin compositions in which thermoplastic resin materials such as polyethylene and polypropylene are mixed with wood flour, which is a biomass material.
[0004] In particular, it is known that semi-carbonizing and finely pulverizing wood flour before mixing with a thermoplastic resin increases the uniform dispersion with the thermoplastic resin, thereby improving moldability (Patent Document 1). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2021 / 193898 Summary of the Invention [Problem to be solved by the invention]
[0006] In general, ultrasonic welding is used to bond resins together. However, for the resin molding material containing roasted wood-based biomass described in Patent Document 1, the strength of ultrasonic welding, which is generally used for moldings of thermoplastic resins such as polyethylene and polypropylene, has not been examined.
[0007] An object of the present invention is to provide a resin molding material containing roasted wood biomass, which has excellent ultrasonic welding strength while reducing the content of synthetic resins derived from petroleum resources, in accordance with the concept of carbon neutrality. [Means for solving the problem]
[0008] The present invention can reduce the content of synthetic resins derived from petroleum resources, and therefore can contribute to the achievement of Goal 7 of the SDGs (Sustainable Development Goals). The present invention relates to, for example, the following [1] to [7]. [1] A material for joining members comprising crushed wood biomass roasted material (A) and a thermoplastic resin (B), The crushed woody biomass roasted material (A) is 3 to 70 mass% in a total of 100 mass% of the crushed woody biomass roasted material (A) and the thermoplastic resin (B), The material for bonding members has a moisture content of 0.02 to 2.00 mass % in 100 mass % of the material for bonding members. [2] The material for joining members according to [1], wherein the crushed material (A) of the roasted wood biomass has an average particle size of 30 to 600 μm. [3] The material for joining members according to [1] or [2], wherein the moisture content in 100% by mass of the crushed material (A) of the roasted wood biomass is 0.1 to 3.8% by mass. [4] The material for joining members according to any one of [1] to [3], wherein the crushed material (A) of wood-based biomass roasted material is 7 to 55 mass% in a total of 100 mass% of the crushed material (A) of wood-based biomass roasted material and the thermoplastic resin (B). [5] The material for bonding members according to any one of [1] to [4], wherein the thermoplastic resin (B) contains a polyolefin resin. [6] A molded product of the material for a joining member according to any one of [1] to [5]. [7] A welding strength improver comprising crushed wood biomass roasted material (A), The water content in 100% by mass of the welding strength improver is 0.02 to 2.00% by mass. Weld strength improver. Effect of the Invention
[0009] The material for joining members of the present invention has excellent ultrasonic welding strength while reducing the content of synthetic resins derived from petroleum resources. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention relates to a material for joining members comprising crushed wood biomass roasted material (A) and a thermoplastic resin (B), The crushed woody biomass roasted material (A) is 3 to 70 mass% in a total of 100 mass% of the crushed woody biomass roasted material (A) and the thermoplastic resin (B), The material for forming joining members has a moisture content of 0.02 to 2.00 mass % in 100 mass % of the material for forming joining members. [Materials for joining components] The material for the joining member includes crushed wood-based biomass roasted material and polypropylene resin.
[0011] [Roasted wood biomass] The wood as the raw material of the woody biomass of the woody biomass torrefaction product is not particularly limited in terms of species and parts, and examples thereof include Douglas fir, Japanese larch, cedar, Japanese cypress, European red pine, old almond trees, almond shells, acacia wood, acacia bark, walnut shells, sago palm, EFB (empty fruit bunches from palm oil processing residue), meranti, rubber trees, etc., and may be one of these or a mixture of two or more of them. It is preferable that the tree species includes spruce.
[0012] Woody biomass torrefaction is a process in which raw woody biomass is roasted. Torrefaction generally refers to a process in which the raw material is heated in a low-oxygen atmosphere at a temperature lower than that of the so-called carbonization process.
[0013] The heating temperature in the roasting of woody biomass to obtain the woody biomass roasted product is appropriately determined depending on the shape and size of the raw biomass and the lump, but is preferably 150 to 400 ° C, more preferably 200 to 350 ° C, even more preferably 230 to 300 ° C, and particularly preferably 250 to 290 ° C. The temperature of the carbonization treatment of normal wood is 400 to 700 ° C, but the woody biomass roasted product (A) is obtained by roasting at the above temperature, so that a woody biomass roasted product having a higher energy density than the raw woody biomass is obtained. In addition, the heating time in the roasting step is not particularly limited, but is preferably 0.2 to 3 hours. In addition, the woody biomass roasted product can also be obtained, for example, by the raw material and manufacturing method described in International Publication WO 2019 / 069849. In the case of wood-based biomass roasted material, solid bridges are formed by roasting, and the connections or adhesion between the biomass powder particles are maintained.
[0014] From the viewpoints of safety and handling, the shape of the woody biomass before roasting is preferably formed into pellets or briquettes by compressing and molding the raw woody biomass. From the viewpoints of safety and handling, the size of the pellets is preferably such that the average long side length is 1 mm or more and 30 mm or less.
[0015] The woody biomass roasted product preferably has a grindability index (HGI) based on JIS M 8801 of 15 or more and 60 or less, more preferably 20 or more and 60 or less. By using a product with an HGI within the above range, the average particle size of the crushed woody biomass roasted product (A) described below can be controlled, which facilitates uniform kneading with the thermoplastic resin (B) and also facilitates molding by injection molding or the like.
[0016] In addition, woody biomass roasted material has a BET specific surface area of 0.15 to 0.8 m 2 / g, and 0.15 to 0.7m 2 / g. Moreover, the equilibrium moisture of the roasted wood biomass after immersion in water is preferably 15 to 65 mass %, more preferably 15 to 60 mass %.
[0017] If the bulk density of the unheated lump of woody biomass before the roasting process is X and the bulk density of the heated solid of woody biomass after the roasting process (crushed woody biomass roasted material (A)) is Y, then Y / X is preferably 0.7 to 1, and more preferably 0.8 to 0.95. The value of the bulk density X is not particularly limited as long as it is within a known range in which unheated lump can be obtained by molding biomass. In addition, the bulk density may be appropriately set since it varies depending on the type of raw material biomass.
[0018] [Crushed woody biomass roasted material (A)] The crushed woody biomass roasted product (A) is obtained by heating and kneading the woody biomass roasted product and the thermoplastic resin (B). The crushed product referred to here may be any product obtained by crushing the woody biomass roasted product from a pellet or briquette-shaped molded body before heating and kneading, and the shape of the crushed product is not particularly limited and may be irregular. From the viewpoint of shortening the manufacturing process, it is preferable to simultaneously crush the woody biomass roasted product while heating and kneading the woody biomass roasted product and the thermoplastic resin (B). On the other hand, from the viewpoint of smoothly feeding the woody biomass roasted product to an optional extruder described later, the woody biomass roasted product may be appropriately pre-pulverized before feeding to obtain a pre-pulverized product, which is then fed into the extruder. The shape of the pre-pulverized product is not particularly limited, and the size may be set to a size that can be fed into an optional extruder described later. For example, the pre-pulverized product may be 15 mm or less, or may be further finely crushed. Examples of the crusher used when crushing the woody biomass torrefied material by preliminary crushing include, but are not limited to, a ball mill, a rod mill, a bead mill, a conical mill, a disk mill, an edge mill, a hammer mill, a mortar, a pellet mill, a VSI mill, a Willy mill, a roller mill, a jet mill, and a mass colloider. The crushed material (A) of the roasted wood biomass can be recovered from the material for the joining member by, for example, a method such as dissolution separation described later.
[0019] The moisture content of the crushed woody biomass roasted material (A) is preferably 0.1 to 3.8 mass%, more preferably 0.1 to 3.0 mass%, further preferably 0.2 to 2.2 mass%, and even more preferably 0.2 to 1.8 mass%, based on 100 mass% of the crushed woody biomass roasted material (A). The moisture content within the above range is preferable in terms of improving the welding strength. The moisture content is measured by a method called Karl Fischer.
[0020] [Average particle size of crushed woody biomass roasted material (A)] The average particle size of the crushed woody biomass roasted material (A) in the material for joining members is preferably 30 to 600 μm, more preferably 50 to 550 μm, even more preferably 120 to 500 μm, and even more preferably 150 to 450 μm. When the average particle size of the crushed woody biomass roasted material (A) is within the above range, the ultrasonic welding strength can be increased. As described above, the shape of the crushed woody biomass roasted material (A) does not need to be granular, and is not particularly limited and may be amorphous. In addition, this average particle size is a value after the woody biomass roasted material and the thermoplastic resin (B) are heated and kneaded. The average particle size referred to here is the 50% average particle size (D50) on a volume basis measured by a laser light scattering method (laser diffraction method) assuming that the crushed woody biomass roasted product (A) has a particle shape, and can be measured using a laser diffraction particle size measuring device (LA-9500V2, Horiba, Ltd.) or the like. The average particle size of the crushed woody biomass roasted product (A) can be controlled, for example, by recovering and measuring the (A) component by a dissolution separation operation, and adjusting the feed position of the woody biomass roasted product to any extruder.
[0021] [Thermoplastic resin (B)] As the thermoplastic resin (B), any resin that can be plasticized and molded by heat can be used, and is not particularly limited, but examples thereof include polypropylene, polyethylene such as low-density polyethylene, linear low-density polyethylene, very low-density polyethylene, and high-density polyethylene, polyolefin resins such as ethylene copolymers, polyacetal resins such as polyoxymethylene, styrene-based elastomers, polyolefin-based elastomers, polyester-based elastomers, and polyamide-based elastomers. The thermoplastic resin (B) is preferably an unmodified resin.
[0022] The thermoplastic resin (B) may be a biodegradable resin. Examples of the biodegradable resin having thermoplasticity include, but are not limited to, polylactic acid (PLA), polyhydroxyalkanoates (PHAs), polybutylene succinate, polyethylene succinate, polyglycol, polycaprolactone, polyvinyl alcohol, and the like. These thermoplastic resins can be used alone, but two or more of them can also be used if desired. Among these, from the viewpoint of moldability, polyolefin resins are preferred, and polyethylene such as LDPE (low density polyethylene) and polypropylene are more preferred.
[0023] The thermoplastic resin (B) may optionally contain a binder resin and a compatibilizing resin. As the compatibilizing resin, known ones may be used, and examples thereof include, but are not limited to, compounds in which a polar group is introduced into a polymer or copolymer of a polyolefin such as maleic anhydride-modified polypropylene or a polyester. Examples of commercially available products include UMEX (registered trademark) 1010 (manufactured by Sanyo Chemical Industries, Ltd.) and MODIC (registered trademark) P908 (manufactured by Mitsubishi Chemical Corporation). The compatibilizing resin functions to improve the uniform mixing and adhesion between the roasted product and the thermoplastic resin.
[0024] As the binder, a known one can be used, and examples thereof include, but are not limited to, polyolefin resins. It is also preferable to use the same resin as the essential thermoplastic resin as the binder and knead it with the crushed woody biomass roasted product (A) before the main kneading. When using the same resin as the essential thermoplastic resin as the binder, it is preferable to knead it with the material for the joining member by excluding the content of the essential thermoplastic resin from the total content of the thermoplastic resin (B) in 100% by mass of the material for the joining member. From the viewpoint of efficiently and effectively utilizing the woody biomass, it is preferable to add the binder in a small amount, preferably 50 parts by mass or less, more preferably 20 parts by mass or less, relative to 100 parts by mass of the woody biomass roasted product.
[0025] In the present invention, the addition of a thermoplastic elastomer is preferable because it makes it possible to stably produce a molding resin with high viscosity that does not cut or crack during injection molding, even when crushed wood biomass roasted material is mixed.
[0026] The thermoplastic elastomer may be a low-crystalline thermoplastic elastomer that does not have a clear yield point, or a non-crystalline thermoplastic elastomer that does not have a clear melting point or yield point and has rubber elasticity at room temperature. Examples of the thermoplastic elastomer include styrene-based elastomers, polyolefin-based elastomers, polyester-based elastomers, and polyamide-based elastomers.
[0027] As the styrene-based elastomer, various types of butadiene-styrene copolymers (random copolymers, block copolymers, graft copolymers) and hydrogenated products thereof, styrene-butadiene-styrene copolymers (SBS), hydrogenated styrene-butadiene-styrene copolymers (SEBS), hydrogenated styrene-butadiene copolymers (HSBR), isoprene-styrene copolymers (random copolymers, block copolymers, graft copolymers) and hydrogenated products thereof, hydrogenated styrene-isoprene copolymers (SEPS), hydrogenated styrene-vinylisoprene copolymers (SIS), hydrogenated styrene-isoprene-styrene copolymers (SEPS), hydrogenated styrene-butadiene rubber (HSBR), and hydrogenated styrene-butadiene-olefin crystalline block copolymers (SEBC) can be used.
[0028] As the polyolefin elastomer, ethylene-propylene rubber (EPR) or ethylene-butene-1 elastomer (EBM) can be used.
[0029] As the polyester-based elastomer, a polyester-polyether copolymer or a polyester-polyester copolymer can be used.
[0030] As the polyamide-based elastomer, a polyamide-polyester copolymer, a polyamide-polyether copolymer, or the like can be used.
[0031] Particularly preferred as the elastomer is hydrogenated styrene-butadiene rubber such as hydrogenated styrene-butadiene-styrene copolymer (SEBS) because of its high compatibility with the propylene-based polymer composition.
[0032] [Optional ingredients] The material for joining members of the present invention may contain, as necessary, reinforcing materials such as glass fibers and carbon fibers, non-plant-based fillers, deterioration inhibitors such as antioxidants and light stabilizers, and lubricants.
[0033] Examples of non-plant-based fillers include inorganic fillers such as marble powder, calcium carbonate, talc, and clay, and metallic fillers such as metal powder.
[0034] Examples of the antioxidant include phenol-based antioxidants, amine-based antioxidants, sulfur-based antioxidants, and phosphorus-based antioxidants.
[0035] Examples of light stabilizers include ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, and cyanoacrylate-based ultraviolet absorbers; hindered amine-based radical scavengers; and quenchers such as nickel complexes.
[0036] Examples of lubricants include hydrocarbon-based lubricants such as liquid paraffin, natural paraffin, microwax, polyethylene wax, etc.; fatty acid amide-based lubricants such as stearic acid amide, palmitic acid amide, methylene bisstearamide, etc.; ester-based lubricants such as butyl arate, hydrogenated castor oil, ethylene glycol monostearate, etc.; alcohol-based lubricants such as cetyl alcohol, stearyl alcohol, etc.; and metal soap-based lubricants such as zinc stearate, calcium stearate, lead stearate, etc.
[0037] In addition, the material for bonding members of the present invention can be mixed with a known foaming agent or foaming assistant, if necessary, so that it can be molded into a foamed molded article. Examples of foaming agents include inorganic ones such as ammonium carbonate and sodium bicarbonate, and organic ones such as dinitrosopentamethylenetetramine, N,N'-dimethyl-N,N'-dinitrosoterephthalate amide, benzenesulfonyl hydrazide, p-toluenesulfonyl hydrazide, p,p'-oxybis(benzenesulfonyl hydrazide), 3,3-disulfonehydrazidephenylsulfone, azobisisobutyronitrile, barium azodicarboxylate, and diethyl azodicarboxylate.
[0038] [Materials for joining members] The material for joining members for welding parts is a material for joining members containing a wood-based biomass roasted material (A) and a thermoplastic resin (B). The material for the joining member can be obtained by blending and mixing or kneading the above-mentioned components. The mixing method may be a conventional method, for example, a method using a ribbon blender, a drum tumbler, a Henschel mixer, a Banbury mixer, a single screw extruder, a twin screw extruder, a co-kneader, a multi-screw extruder, etc. The heating temperature during kneading is usually in the range of 180 to 240°C.
[0039] The blending amount of the crushed woody biomass roasted material (A) and the thermoplastic resin (B) in the material for joining members is 3 to 70 mass%, preferably 5 to 60 mass%, and more preferably 7 to 55 mass%, when the total mass of the crushed woody biomass roasted material (A) and the thermoplastic resin (B) is 100 mass%. By making the content of the crushed woody biomass roasted material (A) 3 mass% or more, the ultrasonic welding strength is increased. In 100% by mass of the material for joining members, the total mass of the crushed wood biomass roasted material (A) and the thermoplastic resin (B) is preferably 70 to 100% by mass, more preferably 80 to 100% by mass, and even more preferably 90 to 100% by mass.
[0040] The shape of the material for forming the joining member before molding is not particularly limited, but is preferably in the form of pellets from the viewpoint of smooth feeding into any extruder.
[0041] The material for joining members has a moisture content of 0.02 to 2.00 mass%, preferably 0.03 to 1.50 mass%, more preferably 0.04 to 1.20 mass%, and even more preferably 0.05 to 1.00 mass% in 100 mass% of the material for joining members. When the moisture content in the material for joining members is within the above range, the ultrasonic welding strength can be increased. The above moisture content is the value after component (A) and component (B) are heated and kneaded. The moisture content of the material for bonding members can be adjusted to the above range by, after heating and kneading component (A) and component (B), performing an operation such as drying, contact with high humidity air, or immersion in water so that the material has a predetermined moisture content. The moisture content of the material for the bonding member can be measured by the Karl Fischer method.
[0042] [Molded body of material for joining components] The material for joining members according to the present invention can be used in the form of various profile extrusion molded bodies, sheets, films, etc. by extrusion molding (not only cold runner type and hot runner type molding methods, but also injection compression molding, injection press molding, gas-assisted injection molding, foam molding (including injection of supercritical fluid), insert molding, in-mold coating molding, heat-insulating mold molding, rapid heating and cooling mold molding, two-color molding, sandwich molding, and injection molding methods such as ultra-high speed injection molding). In addition, the inflation method, calendar method, casting method, etc. can be used for molding sheets and films. Furthermore, it is also possible to mold it into a heat-shrinkable tube by applying a specific stretching operation. The material for joining members according to the present invention can also be made into a hollow molded body by rotational molding, blow molding, etc. The molded body of the material for bonding members has a moisture content of 0.02 to 2.00 mass%, preferably 0.03 to 1.50 mass%, more preferably 0.04 to 1.20 mass%, and even more preferably 0.05 to 1.00 mass% in 100 mass% of the molded body. When the moisture content in the molded body is within the above range, the ultrasonic welding strength can be increased. The moisture content of the molded body can be adjusted to the above range by performing operations such as drying, contact with high humidity air, and immersion in water after molding the material for bonding members according to the present invention so that the moisture content is a predetermined amount.
[0043] There are no particular limitations on each molding method as long as the molded body of the material for bonding members satisfies the above moisture content. The heating temperature for obtaining the molded body is, for example, preferably 160 to 270° C., more preferably 170 to 250° C., and even more preferably 180 to 230° C. The molding conditions for injection molding are, for example, preferably a cylinder temperature of 180 to 230° C. and a mold temperature of 10 to 80° C.
[0044] [Applications of materials for joining components] The molded article of the material for bonding members of the present invention can be used as a resin product formed into exterior materials for office automation equipment and home appliances, for example, exterior materials for personal computers, notebook computers, game consoles, display devices (CRT, liquid crystal, plasma, projectors, organic EL, etc.), mice, printers, copy machines, scanners, faxes (including multifunction devices thereof), keyboard keys, switch molded products, personal digital assistants (so-called PDAs), mobile phones, portable books (dictionaries, etc.), portable televisions, drives for recording media (CDs, MDs, DVDs, next-generation high-density disks, hard disks, etc.), readers for recording media (IC cards, smart media, memory sticks, etc.), optical cameras, digital cameras, parabolic antennas, power tools, VTRs, irons, hair dryers, rice cookers, microwave ovens, audio equipment, lighting equipment, refrigerators, air conditioners, air purifiers, negative ion generators, and typewriters. It is also useful for trays, cups, plates, shampoo bottles, OA housings, cosmetic bottles, beverage bottles, oil containers, injection molded products (golf tees, cotton bud cores, candy sticks, brushes, toothbrushes, helmets, syringes, plates, cups, combs, razor handles, tape cassettes and cases, disposable spoons and forks, stationery such as ballpoint pens, etc.), etc. It is useful for automobile parts, medical instruments, packaging materials, nonwoven fabrics, etc. that undergo ultrasonic welding after molding.
[0045] It can also be used in a wide range of applications, such as cable ties (cable ties), prepaid cards, balloons, pantyhose, hair caps, sponges, cellophane tape, umbrellas, raincoats, plastic gloves, hair caps, ropes, tubes, foam trays, foam cushioning material, cushioning material, packaging material, and cigarette filters.
[0046] Furthermore, the material can be used for various containers, miscellaneous goods, lamp sockets, lamp reflectors, lamp housings, instrument panels, center console panels, deflector parts, car navigation parts, car audio visual parts, auto mobile computer parts, and other vehicle parts.
[0047] In ultrasonic welding, which is generally known to have low welding strength, the resin molded product molded from the material for joining members of the present invention has increased welding strength by ultrasonic welding by containing the roasted wood biomass (A). Since resins can be easily and strongly joined simultaneously at multiple locations using ultrasonic energy, it is possible to be free from the deterioration of the working environment associated with the use of adhesives in the past and the need for complicated bonding processing, and it is possible to efficiently assemble and join fillers in a safe and hygienic working environment.
[0048] [Welding strength improver] Another aspect of the present invention is a welding strength improver containing crushed woody biomass roasted material (A), the moisture content of which is 0.02 to 2.00 mass% in 100 mass% of the welding strength improver. The crushed woody biomass roasted material (A) is the same as that used in the material for joining members. The moisture content in 100% by mass of the crushed material (A) of the roasted wood biomass and the method for adjusting the moisture content are the same as those of the material for the joining member. The weld strength improver preferably contains a thermoplastic resin (B) which is the same as that used in the material for the joining member. EXAMPLES
[0049] The present invention will now be described in detail with reference to examples, but the scope of the present invention is not limited to these examples.
[0050] <Roasted wood biomass> The following components were used for the woody biomass roasted material. MUCC Torrefied Pellets (registered trademark); Torrefied pellets manufactured by UBE Mitsubishi Cement Corporation
[0051] <Polypropylene resin> The polypropylene resin used had the following components: MA1B; Japan Polypropylene Corporation polypropylene: homo PP; MFR (230℃ / 2.16kg) 21g / 10min
[0052] <Polypropylene sheet> The polypropylene sheet used the following components: Polypropylene sheet; PP made by Engineering Test Services: Dimensions 0.3mm x 190mm x 190mm
[0053] <Injection molding conditions> In the examples and comparative examples, injection molding was carried out using an injection molding machine Micro-3 manufactured by Meiho Co., Ltd., in accordance with JIS K6921-2 under the following conditions. Cylinder temperature 200℃, mold temperature 40℃
[0054] [Examples and Comparative Examples] (Production example) Roasted wood biomass was pre-crushed using a Henschel mixer, and the pre-crushed material with an average particle size of 15 mm or less was used in the examples and comparative examples.
[0055] Example 1 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) and polypropylene resin MA1B (50 parts by mass) were melt-kneaded at 180°C to 230°C, both by top feed, to obtain a mixture. The obtained mixture (20 parts by mass) and polypropylene resin MA1B (80 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 50 μm. The material for the joining member was injection molded using a small injection molding machine and vacuum dried at 100°C for 8 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0056] Example 2 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) and polypropylene resin MA1B (50 parts by mass) were melt-kneaded at 180°C to 230°C, both by top feed, to obtain a mixture. The obtained mixture (20 parts by mass) and polypropylene resin MA1B (80 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 50 μm. The material for the joining member was injection molded using a small injection molding machine and left to stand for 72 hours in a constant temperature and humidity room at a temperature of 23°C and a humidity of 50% to obtain a plate (molded body) of 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate (molded body) at two points with a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0057] Example 3 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) and polypropylene resin MA1B (50 parts by mass) were melt-kneaded at 180°C to 230°C, both by top feed, to obtain a mixture. The obtained mixture (20 parts by mass) and polypropylene resin MA1B (80 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 50 μm. The material for the joining member was injection molded using a small injection molding machine and soaked in pure water for 72 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0058] Example 4 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a mixture. The obtained mixture (20 parts by mass) and polypropylene resin MA1B (80 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 300 μm. The material for the joining member was injection molded using a small injection molding machine and vacuum dried at 100°C for 8 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0059] Example 5 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a mixture. The obtained mixture (20 parts by mass) and polypropylene resin MA1B (80 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 300 μm. The material for the joining member was injection molded using a small injection molding machine, and left to stand for 72 hours in a constant temperature and humidity room at a temperature of 23°C and a humidity of 50%, to obtain a plate (molded body) of 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa, to obtain a welded molded product.
[0060] Example 6 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a mixture. The obtained mixture (20 parts by mass) and polypropylene resin MA1B (80 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 300 μm. The material for the joining member was injection molded using a small injection molding machine and soaked in pure water for 72 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0061] Example 7 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a mixture. The obtained mixture (40 parts by mass) and polypropylene resin MA1B (60 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 300 μm. The material for the joining member was injection molded using a small injection molding machine and vacuum dried at 100°C for 8 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0062] Example 8 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a mixture. The obtained mixture (40 parts by mass) and polypropylene resin MA1B (60 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 300 μm. The material for the joining member was injection molded using a small injection molding machine, and left to stand for 72 hours in a constant temperature and humidity room at a temperature of 23°C and a humidity of 50%, to obtain a plate (molded body) of 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa, to obtain a welded molded product.
[0063] Example 9 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a mixture. The obtained mixture (40 parts by mass) and polypropylene resin MA1B (60 parts by mass) were dry-blended to obtain a material for a joining member. The average particle size of the crushed woody biomass roasted material in the material for a joining member was 300 μm. The material for the joining member was injection molded using a small injection molding machine and soaked in pure water for 72 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0064] Example 10 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was top-fed, and melt-kneaded at 180°C to 230°C to obtain a material for joining members. The average particle size of the crushed woody biomass roasted material in the material for joining members was 300 μm. The material for the joining member was injection molded using a small injection molding machine and vacuum dried at 100°C for 8 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0065] Example 11 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was side-fed, and melt-kneaded at 180°C to 230°C to obtain a material for joining members. The average particle size of the crushed woody biomass roasted material in the material for joining members was 300 μm. The material for the joining member was injection molded using a small injection molding machine, and left to stand for 72 hours in a constant temperature and humidity room at a temperature of 23°C and a humidity of 50%, to obtain a plate (molded body) of 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa, to obtain a welded molded product.
[0066] Comparative Example 1 Polypropylene resin MA1B was injection molded using a small injection molding machine to obtain a plate (molded product) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0067] Comparative Example 2 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) and polypropylene resin MA1B (50 parts by mass) were melt-kneaded at 180°C to 230°C using a top feed to obtain a material for joining members. The average particle size of the crushed woody biomass roasted material in the material for joining members was 50 μm. The material for the joining member was injection molded using a small injection molding machine and soaked in pure water for 72 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0068] Comparative Example 3 The pre-crushed woody biomass roasted material obtained in the manufacturing example (50 parts by mass) was side-fed, and polypropylene resin MA1B (50 parts by mass) was side-fed, and melt-kneaded at 180°C to 230°C to obtain a material for joining members. The average particle size of the crushed woody biomass roasted material in the material for joining members was 300 μm. The material for the joining member was injection molded using a small injection molding machine and soaked in pure water for 72 hours to obtain a plate (molded body) 30 mm square and 2 mm thick. A polypropylene sheet was ultrasonically welded to the plate at two points using a small ultrasonic welding machine (AUH30CW, manufactured by Suzuki Corporation) at a pressure of 3.0 kPa to obtain a welded molded product.
[0069] The compositions of the examples and comparative examples were measured and evaluated by the following methods. (Moldability) Moldability was judged based on whether or not a plate could be molded using a small injection molding machine. A check mark indicates a pass and a check mark indicates a fail. 〇: Plates can be molded without any problems. ×: Poor molding or molding not possible.
[0070] (Measurement of average particle size) The average particle size of the crushed wood biomass roasted material before mixing and the average particle size of the crushed wood biomass roasted material in the material for joining members were measured using a laser diffraction particle size analyzer (LA-9500V2, Horiba, Ltd.), and the 50% particle size based on volume was taken as the average particle size.
[0071] (Evaluation of ultrasonic welding strength) (Tensile test) The welded molded product was subjected to a tensile test using an Instron universal testing machine in accordance with ISO-527 to measure the strength at which the polypropylene sheet peeled off from the plate.
[0072] (Method for measuring moisture content of materials for joining components) Using a Karl Fischer moisture meter (manufactured by Nitto Seiko Air Analytec Co., Ltd.), the moisture content of the injection-molded product (molded body) of the material for joining members was measured under conditions of a temperature of 215°C, an end-point titration rate of 0.95 μg / s, and nitrogen gas of 250 ml / min.
[0073] (Method of calculating the moisture content of crushed woody biomass roasted material) Under the above-mentioned measurement conditions, the moisture content of the molded body of the material for joining members was measured, and the moisture content per unit mass was calculated. Similarly, the moisture content of the molded body obtained only from polypropylene resin was measured, and the moisture content per unit mass was calculated. From the difference between these, the moisture content in the crushed wood-based biomass roasted material contained in the molded body of the material for joining members per unit mass was calculated. The molded body of polypropylene resin used in this calculation is the molded body obtained in Comparative Example 1.
[0074] [Table 1]
[0075] From Table 1, we can see the following: By comparing Example 1 and Comparative Example 1, it was found that the ultrasonic welding strength was increased by including the roasted wood biomass material (A) and the polypropylene resin (B). By comparing the Example with Comparative Examples 2 and 3, it was found that the ultrasonic welding strength can be increased by keeping the moisture content in the material within a certain range. By comparing Example 1 with Example 4, it was found that the ultrasonic welding strength increases when the particle size of the roasted wood biomass material (A) is larger.
Claims
1. A material for joining members comprising crushed wood biomass roasted material (A) and a thermoplastic resin (B), The crushed woody biomass roasted material (A) is 3 to 70 mass% in a total of 100 mass% of the crushed woody biomass roasted material (A) and the thermoplastic resin (B), The material for joining members has a moisture content of 0.02 to 2.00 mass% in 100 mass% of the material for joining members.
2. The material for joining members according to claim 1, wherein the crushed material (A) of the wood-based biomass roasted material has an average particle diameter of 30 to 600 μm.
3. The material for joining members according to claim 1 or 2, wherein the moisture content in 100% by mass of the crushed material (A) of the wood-based biomass roasted material is 0.1 to 3.8% by mass.
4. The crushed wood biomass roasted material (A) is 7 to 55 mass% in a total of 100 mass% of the crushed wood biomass roasted material (A) and the thermoplastic resin (B). The material for joining members according to claim 1 or 2.
5. The material for bonding members according to claim 1 or 2, wherein the thermoplastic resin (B) contains a polyolefin resin.
6. A molded article of the material for joining members according to claim 1 or 2.
7. A welding strength improver comprising crushed wood biomass roasted material (A), The water content in 100% by mass of the welding strength improver is 0.02 to 2.00% by mass. Weld strength improver.
Citation Information
Patent Citations
Resin material for molding use and method for producing same
WO2021193898A1